Mouse Wnt1‐CRE‐RosaTomato Dental Pulp Stem Cells Directly Contribute to the Calvarial Bone Regeneration Process. (13th March 2019) - Collignon, Anne‐Margaux; Castillo‐Dali, Gabriel; Gomez, Eduardo; Guilbert, Thomas; Lesieur, Julie; Nicoletti, Antonino; Acuna‐Mendoza, Soledad; Letourneur, Didier; Chaussain, Catherine; Rochefort, Gael Y.; Poliard, Anne
Abstract: Stem cells endowed with skeletogenic potentials seeded in specific scaffolds are considered attractive tissue engineering strategies for treating large bone defects. In the context of craniofacial bone, mesenchymal stromal/stem cells derived from the dental pulp (DPSCs) have demonstrated significant osteogenic properties. Their neural crest embryonic origin further makes them a potential accessible therapeutic tool to repair craniofacial bone. The stem cells' direct involvement in the repair process versus a paracrine effect is however still discussed. To clarify this question, we have followed the fate of fluorescent murine DPSCs derived from PN3 Wnt1‐CRE ‐ Rosa Tomato mouse molar (T‐mDPSCs) during the repair process of calvaria bone defects. Two symmetrical critical defects created on each parietal region were filled with (a) dense collagen scaffolds seeded with T‐mDPSCs, (b) noncellularized scaffolds, or (c) no scaffold. Mice were imaged over a 3‐month period by microcomputed tomography to evaluate the extent of repair and by biphotonic microscopy to track T‐mDPSCs. Histological and immunocytochemical analyses were performed in parallel to characterize the nature of the repaired tissue. We show that T‐mDPSCs are present up to 3 months postimplantation in the healing defect and that they rapidly differentiate in chondrocyte‐like cells expressing all the expected characteristic markers. T‐mDPSCs further maturate into hypertrophic chondrocytes and likely signal to host progenitors that form new bone tissue. This demonstrates that implanted T‐mDPSCs are able to survive in the defect microenvironment and to participate directly in repair via an endochondral bone ossification‐like process. Stem Cells 2019;37:701–711 Abstract : Wnt1‐CRE‐RosaTomato DPSC were implanted in a calvaria critical‐sized defect and shown by microCT, biphotonic and immunohistochemical analyses to participate in bone repair through an endochondral process